2019
DOI: 10.1039/c8nj04196b
|View full text |Cite
|
Sign up to set email alerts
|

1IL and 3MLCT excited states modulated by H+: the structure and photophysical properties of [(2-bromo-5-(1H-pyrazol-1-yl)pyrazine)Re(CO)3Br]

Abstract: The photophysical characterization of pyrazolyl–pyrazine Re(i) complex, shows a 1IL and 3MLCT excited states, being just the 3MLCT able to react with trifluoroacetic acid to yield the protonated and long-lived 3ILH+ species. These findings make the compound a potential sensor for protons in solution in the presence of light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Additionally, complex III shows a second reduction wave at −1.90 V, consistent with a Re I /Re 0 couple. This has been previously described for tricarbonyl Re I complexes with different diimine derivates. , …”
Section: Results and Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Additionally, complex III shows a second reduction wave at −1.90 V, consistent with a Re I /Re 0 couple. This has been previously described for tricarbonyl Re I complexes with different diimine derivates. , …”
Section: Results and Discussionsupporting
confidence: 65%
“…This has been previously described for tricarbonyl Re I complexes with different diimine derivates. 27,64 The values for the reduction potential show to be increasingly more negative going from II to V. This means R 1 : = H (I) to N-methylpyrazolyl (V) (Scheme 1). To define the influence of these substituents, we have compared the difference between E p,c and E p,a with the HOMO−LUMO gap as determined from DFT modeling (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyrazolyl derivatives are appealing candidates to be explored, mainly due to their planarity and limited conformational flexibility that will diminish non-radiative deactivation paths [27,28]. We have recently shown that substitution modifications over this skeleton would modulate the electronic structure and in consequence, the compound properties [29,30]. Thus, this kind of compounds provides unique opportunities to rationally address their properties by finely tuning through modification of the ligands.…”
Section: Introductionmentioning
confidence: 99%